An Effective Chromosome Representation on Proportional Tuition Fees Assessment Using NSGA-II - Jauhari, Farid; Mahmudy, Wayan Firdaus; Basuki, Achmad (Faculty of Computer Science (FILKOM) Brawijaya University, 2019)
Proportional tuition fees assessment is an optimization process to find a compromise point between student willingness to pay and institution income. Using a genetic algorithm to find optimal solutions requires effective chromosome representations, parameters, and operator genetic to obtain efficient search. This paper proposes a new chromosome representation and also finding efficient genetic parameters to solve the proportional tuition fees assessment problem. The results of applying the new chromosome representation are compared with another chromosome representation in the previous study. The evaluations show that the proposed chromosome representation obtains better results than the other in both execution time required and the quality of the solutions.